Toxicity after radiotherapy in patients with historically accepted contraindications to treatment (CONTRAD): An international systematic review and meta-analysis. (June 2019) - Lin, Diana; Lehrer, Eric J.; Rosenberg, Jennifer; Trifiletti, Daniel M.; Zaorsky, Nicholas G.
Highlights: Collagen vascular disease and inflammatory bowel disease are "historically accepted" contraindications to radiotherapy. In this meta-analysis of 621 patients with these disorders, grade 4 toxicity across both diseases was 1.5% and 4.5% for acute and late toxicities, respectively. Thus, collagen vascular disease and inflammatory bowel disease are not absolute contraindications to radiotherapy. Abstract: Background and purpose: To investigate the incidence of radiotherapy-related acute and late toxicities among patients with pro-inflammatory comorbidities. Material and methods: PICOS/PRISMA/MOOSE methods were used to identify studies on PubMed and MEDLINE, 1970–2018. The following were extracted: location, cancer, sample size, age, follow-up duration, medical contraindication, treatment, and toxicity. A weighted random effects model with the DerSimonian and Laird method was used in the meta-analysis. The primary endpoint was the grade ≥ 3 acute toxicity, and the secondary endpoint was late toxicity. Results: There were 1137 articles screened and 18 included, assessing 621 patients. Among the 18 articles, 10 had collagen vascular disease ( n  = 417) and 8 had inflammatory bowel disease ( n  = 204). Median follow-up was 52.8 months. 457 patients received radiotherapy alone, and 153 received concurrent chemo-radiotherapy. The random effects estimate for incidence of grade ≥ 3 toxicity in collagen vascular disease patients (95% confidence interval) was 11.7% (5.4–19.6%) and 6.1% (1.4–12.6%) for acute and late toxicities, respectively. Incidence of grade ≥ 3 toxicity in inflammatory bowel disease patients was 14.0% (7.1–22.4%) and 10.2% (3.2–19.7%) for acute and late toxicities, respectively. Average grade 4 toxicity across both diseases was 1.5% and 4.5% for acute and late toxicities, respectively. Average grade 5 toxicity across both diseases was negligible (<1%). Conclusions: Patients with historically accepted contraindications to radiation therapy have a 10–15% risk of any grade ≥ 3 toxicity, <5% risk of grade 4 toxicity, and <1% risk for grade 5 toxicity, suggesting that collagen vascular disease and inflammatory bowel disease are not absolute contraindications to radiotherapy.